925 Is Routine Bloods Group and Save Required for Emergency Appendicectomy?. (4th May 2021) - Karim, S; Shah, V; Adegbola, S; Tewari, S; Gupta, V
Abstract: Introduction: Appendicectomy is commonly a safe and low bleeding risk procedure. However, some hospital guidelines stipulate a requirement for routine pre-operative blood group and save (G&S).We aim to determine if pre-operative G&S is required for appendicectomies by looking at the number of tests vs transfusion conducted.The cost of G&S is £4.14 per sample in our trust. Method: A retrospective review was conducted over a 3-month period. Patient data and demographics were identified using the hospital coding, theatre records and transfusion departments. Results: 118 consecutive appendicectomies were identified. Of which, 99 laparoscopic vs 19 open (13 started open vs 6 converted to open) operations were performed. No patients required a blood transfusion during their admission. There was a total of 219 G&S conducted. Cross matching tests for these procedures cost a total of £906. We estimate a cost projection of £3624 for G&S tests over a year and £18120 over 3 years. Conclusions: Bleeding complications requiring transfusion following appendicectomies are very uncommon. In our unit, 0% of patients identified required a transfusion during their admission. We suggest stopping routine pre-operative G&S for these patients would be clinically safe and would lead to financial savings and reduce pre-operative waiting time.